Burrow morphology of Uca uruguayensis and Uca leptodactylus (Decapoda: Ocypodidae) from a subtropical mangrove forest in the western Atlantic - Machado, Glauco B. O. [UNESP]; Gusmao-Junior, Joao B. L. [UNESP]; Costa, Tania M. [UNESP] (Wiley-Blackwell, 2013)
The continuous excavation of burrows by fiddler crabs generates bioturbation in the sediment, which can be estimated from burrow morphology. The aim of the present study was to describe the burrow morphology of Uca uruguayensis and U. leptodactylus and its relationship with demography of resident individuals and to estimate the level of bioturbation in the sediment generated by each species. For all individuals from each of the 2 species, sex was determined and the carapace width (CW; mm) measured. Burrows were characterized according to burrow diameter (BD; mm), maximum burrow depth (MBD; mm) and burrow volume (BV; cm(3)). The density of each species in the study area was also evaluated. In both species, the males were larger and occupied burrows with higher BV compared to females. Differences between sexes in relation to the burrow characteristics might reflect sexual dimorphism within the group and are probably related to the fact that males use the burrows for mating. BD and BV showed significant positive relationships with the size of resident crabs. The amount of sediment removed per burrow was estimated from mean BV: 10.78 cm(3) of sediment/burrow for U. uruguayensis and 12.38 cm(3) of sediment/burrow for U. leptodactylus. Despite the density and depth differences between the 2 species, the similarity in burrow volume suggests that U. uruguayensis and U. leptodactylus present the same importance in terms of the bioturbation process. Burrow morphology is highly associated with characteristics of the occupant, although extrinsic factors should also be considered, and its description can provide estimates on the bioturbation generated by Uca species in mangrove forests.
Keywords: bioturbation; burrow structure; crab burrowing; fiddler crab